Analisis Karakter Toleransi dalam Pembelajaran Suhu dan Kalor Berbasis Budaya Lokal Ruwatan Rambut Gimbal - Ayu Mar’ati Barokatun Ni’mah; Sri Jumini; Anik Zuhriatul Fatimah (Jurnal Kreatif Online, 2022)
This study aims to determine the character of tolerance in learning temperature and heat based on local culture of dreadlocks treatment. The research method used was qualitative research and the data collection techniques was literature review. The research findings were in the form of various tolerance characters that were generated in the implementation of culture-based learning, namely dreadlocks treatment. The conclusion of the study shows that there are several tolerance characters that can be increased through temperature and heat based on local culture of dreadlocks treatment, they are mutual respect for differences, peace, awareness, as well as a sense of love for one's own culture.